Quick recipes on Symbian OS : mastering C++ smartphone development - Aubert, Michael (Symbian Press., 2008)
"Whether you need to port a desktop application, create a quick prototype or simply want to learn about application development in the mobile space, this book is both the perfect introduction to Symbian OS and an excellent reference guide. The book is like a cookbook, with self-contained chapters covering common programming tasks. Each section explains the length of time needed to implement the code, and its difficulty level. Tasks are explained in detail, and snippets of example code provided. The full sample code is provided for download so it can be used as a starting point in your own projects."--Jacket